The Melting Snowball Effect: A Heuristic for Sustainable Arctic Governance Under Climate Change - Dankel, Dorothy J.; Tiller, Rachel G.; Koelma, Elske; Lam, Vicky W. Y.; Liu, Yajie (Frontiers in Marine Science, 2020)
Climate change in the Arctic is occurring at a rapid rate. In Longyearbyen, Svalbard, the world’s northernmost city, deadly avalanches and permafrost thaw-induced architectural destruction has disrupted local governance norms and responsibilities. In the North Atlantic, the warming ocean temperatures have contributed to a rapid expansion of the mackerel stock which has spurred both geo-political tensions but also tensions at the science-policy interface of fish quota setting. These local climate-induced changes have created a domino-like chain reaction that intensifies through time as a warming Arctic penetrates deeper into responsibilities of governing institutions and science institutions. In face with the increasing uncertain futures of climate-induced changes, policy choices also increase revealing a type of “snowballing” of possible futures facing decision-makers. We introduce a portmanteau-inspired concept called “The Melting Snowball Effect” that encompasses the chain reaction (“domino effect”) that increases the number of plausible scenarios (“snowball effect”) with climate change (melting snow, ice and thawing permafrost). We demonstrate the use of “The Melting Snowball Effect” as a heuristic to create plausible scenarios for deliberative discussions among academics, citizens and policymakers. We apply this heuristic in a Responsible Research and Innovation (RRI) framework to underscore anticipation, engagement and reflection needed by publics to increase the capacity of democracies to sustainably adapt to climate change. We observe generational differences in discussing future climate scenarios, particularly that the mixed group where three generations were represented had the most diverse and thorough deliberations.